Análisis de una prótesis no convencional bloqueada para cadera mediante el método del elemento finito - Domínguez-HernándeZ, Víctor Manuel; Carbajal Romero, Manuel Faraón; Rico Martínez, Genaro; Urriolagoitia Calderón, Guillermo (Revista Mexicana de Ingenieria Biomedica, 2003)
A finite element model of a coupled bone-non-conventional prosthesis system was developed. The implant is mainly employed in the treatment of tumors that affect the proximal end of the femur, being instability the main disadvantage of this implant. The geometry of the femur was established by means of sixty tomographic scans using Ansys software, version 5.7. Afterward, a bone-prosthesis model was integrated with 19895 elements and 34154 nodal points. We examined four cases, in the first three cases only hip joint reaction force was considered and a proximal pin was placed at 50, 25 and 75 mm from the osteotomy site. A distal pin was placed 25 mm from the proximal in all cases. A fourth case considered additionally abductor muscle force, with the proximal pin placed at 50 mm. We found that as pins approach the osteotomy site, stresses induced within pins are increased at the same rate. The fourth case presented the best results, followed by case 1, 2 and 3. Since current practice does not permit to attach abductor muscle directly to the implant, case 1 is the best option, however, our results encourage research directed to restore abductor lever and improve implant stability.